Psychological features of shyness in preschool children - Bondarchu, Oksana (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2020)
The article provides a theoretical and empirical analysis of the psychological characteristics of the manifestation of shyness in preschool children. Analyzed the scientists' views on understanding of the studied phenomenon, the classification of pathological and personal forms of manifestation of personality shyness is considered. The psychological characteristics of "internally" and "externally" shy preschoolers are characterized. The positive and negative influence of shyness on the mental development of a preschool child has been substantiated. Based on a theoretical analysis of psychological literature, has given its own definition of the concept of personal shyness of a preschooler. With the help of the conducted empirical research, the structural components of personal shyness in preschool children were identified. In preschool, shyness can take the form of "internal" or "external" introspection and stimulate the search for optimal ways to overcome negative experiences using primitive isolation, autistic fantasies, etc. In our opinion, shyness in preschool children is an integrated personal quality, which is a component of emotional and volitional behavior of the child and manifests itself in the form of low self-esteem, underdeveloped communication skills, fear, need for external support and intrapersonal conflicts. The components of the self-concept of a shy preschooler have their own specific features: behavioral is characterized by fear of novelty, insecurity, conformity, lack of initiative, neglect of joint play activities, etc .; affective-evaluative component - insecurity, anxiety, timidity, anxiety, loneliness, fear of social contacts, dependence on the assessments of others, emotional vulnerability to failure; the communicative component is characterized by silence, limitations, selectivity or avoidance of interaction, inability to maintain long-term contacts, express their own opinions, etc.The results of our observational experiment showed that the presence of indicators characteristic of a high level of personal shyness was found in 21.15% of preschool children, the average level of formation in 37.63% of subjects and a low level of shyness in preschool age was found in 41.22% of children.
Keywords: preschooler; self-esteem; shyness; communication; fear